Inflammatory Immune Responses and Gut Microbiota Changes Following Campylobacter coli Infection of IL-10-/- Mice with Chronic Colitis - Markus M. Heimesaat; Claudia Genger; Nina Biesemeier; Sigri Klove; Dennis Weschka; Soraya Mousavi; Stefan Bereswill (Pathogens, 2020)
Human infections with the food-borne enteropathogens Campylobacter are progressively rising. Recent evidence revealed that pre-existing intestinal inflammation facilitates enteropathogenic infection subsequently exacerbating the underlying disease. Given that only little is known about C. coli–host interactions and particularly during intestinal inflammation, the aim of the present study was to survey gastrointestinal colonization properties, gut microbiota changes and pro-inflammatory sequelae upon peroral C. coli-infection of IL-10-/- mice with chronic colitis. C. coli colonized the gastrointestinal tract of mice with varying efficiencies until day 28 post-infection and induced macroscopic and microscopic inflammatory changes as indicated by shorter colonic lengths, more distinct histopathological changes in the colonic mucosa and higher numbers of apoptotic colonic epithelial cells when compared to mock-infected controls. Furthermore, not only colonic innate and adaptive immune cell responses, but also enhanced systemic TNF-α secretion could be observed following C. coli as opposed to mock challenge. Notably, C. coli induced intestinal inflammatory sequelae were accompanied with gut microbiota shifts towards higher commensal enterobacterial loads in the infected gut lumen. Moreover, the pathogen translocated from the intestinal tract to extra-intestinal tissue sites in some cases, but never to systemic compartments. Hence, C. coli accelerates inflammatory immune responses in IL-10-/- mice with chronic colitis.